2011
DOI: 10.1111/j.1466-7657.2011.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of stress in nursing students: a systematic review of quantitative studies

Abstract: Aim: This study aimed to identify the main sources of stress for students of nursing and the evolution of the stressors when training in nursing competences. Background: Levels of stress are higher for health professionals than for other workers. A higher number of stressors with negative health consequences are present, especially among nursing professionals. Stress is a psychosocial factor that influences the academic performance and well-being of this group. The interest in analysing sources of stress in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
280
2
36

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(331 citation statements)
references
References 36 publications
13
280
2
36
Order By: Relevance
“…[1] Although growing literature view nursing clinical practice as a stressful experience that can cause negative consequences on both students' academic performance as well as their well-being. [2][3][4][5] Stress experienced by nursing students has profound effects on educational programs, on nurse employers, and the entire nursing profession. Stress not only jeopardize students' competencies, increase nursing shortage via increasing intention to leave the profession, but also endanger the entire quality of healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Although growing literature view nursing clinical practice as a stressful experience that can cause negative consequences on both students' academic performance as well as their well-being. [2][3][4][5] Stress experienced by nursing students has profound effects on educational programs, on nurse employers, and the entire nursing profession. Stress not only jeopardize students' competencies, increase nursing shortage via increasing intention to leave the profession, but also endanger the entire quality of healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The most common sources of this distress are, among others, their workload and problems associated with their studies, fear of unknown situations and difficulties during their clinical practices (6) . In addition, students must embody certain personal factors (assertiveness, being able to say no, confrontation, self-esteem and social relationships) that involve multiple and significant adaptations that they must adequately and immediately make during their training period (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…In a few instances, distress has been evaluated by measuring burnout syndrome (6,15) . Academic engagement is a construct that is considered to be the opposite of burnout syndrome (16) , and examining it can indicate whether academic engagement positively influences the student's psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Pulido-Martos and colleagues (2011) conducted a systematic review of the quantitative literature to reveal sources of nursing student stress. [23] They found that "the most common source[s] of stress relate to academics (reviews, workload and problems associated with studying)" (p. 15). Researchers who explored first year nursing students' sources of stress reported the following categories: "intrapersonal", "interpersonal", "academic", and "environmental" with the most frequently reported being "academic" stress.…”
Section: Stressmentioning
confidence: 99%